Photo- and radioluminescence of poleskiy amber - Mysiura, I.; Kalantaryan, O.; Kononenko, S.; Zhurenko, V.; Grigorenko, D.; Chishkala, V.; Azarenkov, N.; Avotin, S.; Rohmanov, N. (Functional Materials, 2016)
The paper presents the results of systematic study of Poliskiy amber luminescence. The experiments were performed with specimens of natural amber with a variety of physical and chemical parameters. The luminescence was excited by UV- or X-ray radiation. The photoluminescence spectra of different specimens are similar and are well approximated by two Gaussian curves with peaks of 2.48 and 2.95 eV. The luminescence spectrum excited by X-ray radiation has a maximum intensity at the wavelength near that for UV excitation, but the shape is significantly different.